Climate change e-module based on socio-scientific issues teaching and learning: A validity and practicality study - Usamah, Moh.; Rohman, Fatchur; Al Muhdhar, Mimien Henie Irawati (JPBIO (Jurnal Pendidikan Biologi), 2025)
Climate change education is a priority in Indonesia's national curriculum. One challenge in teaching climate change in biology classes is the limited availability of teaching materials that cover various socio-scientific issues. Further development of these teaching materials is needed. This study aimed to develop a Climate Change E-Module based on Socio-Scientific Issues Teaching and Learning (SSI-TL) and test its validity and practicality in the learning process. This Research and Development (R&D) study used the Lee & Owens model, which focuses on developing multimedia-based learning designs. The e-module was created using Google Sites. Subject matter experts, media experts, and biology education practitioners assessed the e-module's validity. Practicality was assessed based on student responses through one-to-one trials, small group trials, and field trials. The validity test results showed the e-module to be highly valid, with percentages of 93% from a subject matter expert, 94% from a media expert, and 96% from a biology education practitioner. Practicality test results showed a highly practical category, with percentages of 87% for the one-to-one trial, 92% for the small group trial, and 93% for the field trial. Thus, the Climate Change E-Module based on SSI-TL is valid and practical for use in biology education.